Association of HSPA1B SNP rs6457452 with Alopecia Areata in the Korean Population. (April 2014) - Seok, Hosik; Jeon, Hye Sook; Park, Hae Jeong; Kim, Su Kang; Choi, Jeong Hwee; Lew, Bark-Lynn; Chung, Joo-Ho; Sim, Woo-Young
<x xml:space="preserve">Abstract</x> The heat shock 70 kDa protein 1B (HSPA1B), which has been well-studied among the famous heat shock proteins HSPA1A/B/L, is related to autoimmune diseases, including Alopecia Areata (AA). In this study, the association of a 5'-untranslated region (5'UTR) SNP rs6457452 and a promoter SNP rs2763979 (‐1140C > T) of HSPA1B with AA was investigated in 236 controls and 228 AA patients. Statistical analyses using the multiple logistic models were done, according to the onset and the clinical features of AA, including the age of onset, family history, type of AA lesion, nail involvement and body hair involvement. The results showed that rs6457452 was associated with the onset of AA (p < 0.002). In the analysis of clinical features of AA, rs6457452 was weakly related to the age of onset (p ≤ 0.04) and that rs2763979 was only weakly related to the type of AA lesion (p = 0.041). In conclusion, we suggest that the 5'UTR SNP rs6457452 of HSPA1B may be associated with the onset of AA and the T allele of rs6457452 may confer the reduced susceptibility to AA in the Korean population.